MULTIMODAL APPROACH TO THE IMAGE OF IMPOVERISHED: A VISUAL ANALYSIS OF COVERS IN A SAMPLE FROM INTERMÓN OXFAM MAGAZINES - María MARTÍNEZ LIROLA,Laura IBÁÑEZ CASTEJÓN,, (Fonseca, Journal of Communication, 2023)
This article intends to approach the way NGOs represent the population in poor and rich countries1 and their own representation as NGOs of Development. Our corpus consists of all the issues from the Intermón Oxfam’s magazine called Revista IO published in 2012. We will offer a detailed analysis of the covers because this is the first page seen by the readers and because this is the way in which the NGO introduces itself.